Efforts to Improve Students Discipline Through Habituation Activities at Minhajut Thalibin Boarding School - Abdunnasir Abdunnasir; Amirudin Amirudin (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
The purpose of efforts to improve student discipline through habituation activities at the Minhajut Thalibin Islamic Boarding School is that habituation of discipline is a process or way to create a habit of disciplined behaviour. And the attitude of discipline will be reflected in the existence of obedience to respect and implement a system that requires people to submit to applicable decisions, orders and regulations. The problem that will be studied in this research is how to improve student discipline through habituation activities at the Minhajut Thalibin Islamic Boarding School. Where this research is field research or field research, the type of research is qualitative. Data collection techniques using observation, interviews and documentation. While the technique used to analyze the data is qualitative data analysis techniques. Efforts to improve student discipline through habituation activities at the Minhajut Thalibin Islamic Boarding School, Patokbeusi District, Subang Regency. The results of the author's research indicate that the habituation of students' disciplined attitudes in educational activities at the Minhajut Thalibin Islamic Boarding School, Patokbeusi District, Subang Regency is carried out through activities from the curriculum section and the student body. For educational activities from the curriculum section, the learning process is carried out six days a week with the provision of a weekly holiday on Friday. The educational activities of the Students division include congregational prayers at the mosque, morning and evening dhikr, sunnah fasting on Mondays and Thursdays, reading of hadith after Maghrib prayers, and practice lectures in muhadhoroh activities. Among the objectives of holding educational activities at the Minhajut Thalibin Islamic Boarding School, Patokbeusi District, Subang Regency, is an effort to habituate the disciplined attitude of the students in the hope that they are accustomed to discipline in carrying out their activities.